Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V - andi nurfaisah; muh anis (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
The research objective was to describe the improvement in social studies learning outcomes of grade V SD Inpres 12/79 Macope students after using the Think Pair Share type cooperative learning model. The approach used is a qualitative approach that is descriptive, this type of research is a classroom action research conducted in two cycles. The focus of research is the social studies learning outcomes of grade V students and the Think Pair Share type of cooperative learning model. The research setting was class V SD Inpres 12/79 Macope. The data analysis technique is descriptive analysis which is carried out by reducing data, presenting data, drawing conclusions, and verification. The results of data analysis indicate that learning using the Think Pair Share type of cooperative learning model can improve social studies results for fifth grade students of SD Inpres 12/79 Macope.